2002
DOI: 10.1093/rheumatology/41.3.329
|View full text |Cite
|
Sign up to set email alerts
|

The role of TNF‐α in the pathogenesis of inflammation and joint destruction in rheumatoid arthritis (RA): a study using a human RA/SCID mouse chimera

Abstract: This study provides strong evidence that TNF-alpha is a key molecule in the control of the inflammatory changes that occur in the RA synovium. In addition, TNF-alpha regulates IL-6 production. However, other inflammatory pathways independent of TNF-alpha may contribute to the bone and cartilage damage seen in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(119 citation statements)
references
References 24 publications
5
113
0
1
Order By: Relevance
“…TNF-α contributes to the RA pathogenesis as a pivotal cytokine , its main source is macrophages of the synovium (Choy & Panayi, 2001;Matsuno et al, 2002). Several studies have shown that the levels of TNF-α correlated with arthritis severity, and that TNF-α neutralizing therapy using Anti-TNF-α monoclonal antibody and soluble TNF receptor improves clinical symptoms and inhibits (or even reverses) inflammatory bone destruction in RA .…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α contributes to the RA pathogenesis as a pivotal cytokine , its main source is macrophages of the synovium (Choy & Panayi, 2001;Matsuno et al, 2002). Several studies have shown that the levels of TNF-α correlated with arthritis severity, and that TNF-α neutralizing therapy using Anti-TNF-α monoclonal antibody and soluble TNF receptor improves clinical symptoms and inhibits (or even reverses) inflammatory bone destruction in RA .…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic minipumps (model 2001, Durect, Cupertino, CA) prefilled with sterile recombinant murine TNF-␣ (R&D Systems, Minneapolis, MN) dissolved in a vehicle solution (physiological saline with 0.1% mouse serum albumin) or vehicle alone (sham) were implanted subcutaneously on the dorsal aspect of mice through a small incision under the skin. These pumps were designed to deliver 1 l/h of TNF-␣ or vehicle alone for 7 days and have been demonstrated to elicit elevated TNF-␣ serum concentrations (31). After the 7-day period, pumps were removed from the mice, and any remaining volume was aspirated.…”
Section: Methodsmentioning
confidence: 99%
“…TNFα is a clinically validated pathogenic factor in inflammatory erosive arthritis in RA and is pivotal target for directed bio logic intervention [3,[21][22][23] . Fragmented hyaluronan is increased in the RA synovium and synovial fluid [24,25] .…”
Section: The Regulation Of P-gp Expression On Lymphocytesmentioning
confidence: 99%
“…The immunosuppressants cyclosporine and tacro limus act as calcineurin inhibitors and inhibit cytokine production promoted by NF-AT, as well as act as P-gpof RA, as it exacerbates erosive synovitis and enhances disease activity, and is thus an excellent molecular target for directed biologic intervention [3,[21][22][23] . Infliximab and etanercept, two highly effective antagonists of TNFα, have revolutionized treatment strategies for RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%